Identifying Potential Human Monoacylglycerol Lipase Inhibitors from the Phytoconstituents of Morinda Citrifolia L. Fruits by in silico Pharmacology and in vitro Study - Sadino A; Saptarini NM; Levita J; Ramadhan DSF; Fristiohady A; Jiranusornkul S (Dove Medical Press, 2024)
Asman Sadino,1,2,* Nyi Mekar Saptarini,3 Jutti Levita,4,* Dwi Syah Fitra Ramadhan,5 Adryan Fristiohady,6 Supat Jiranusornkul7 1Doctoral Program in Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Mathematics and Natural Sciences, Garut University, Garut, West Java, 44151, Indonesia; 3Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, West Java, Indonesia; 5Department of Pharmacy, Poltekkes Kemenkes Makassar, Makassar, South Sulawesi, 90222, Indonesia; 6Faculty of Pharmacy, Halu Oleo University, Kendari, Southeast Sulawesi, 93132, Indonesia; 7Department of Pharmaceutical Science, Faculty of Pharmacy, Chiang Mai University, Chiang Mai, Thailand*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 46363, Indonesia, Email jutti.levita@unpad.ac.idBackground: Human monoacylglycerol lipase (MGL) is accountable for the hydrolysis of 2-arachidonoylglycerol (2-AG), thus contributing pivotally to neuroprotection because 2-AG is the main source of arachidonic acid, the precursor of prostaglandins production. Inhibiting MGL reduces inflammatory damage in the ischemic brain and enhances cerebral blood flow. Plants have been reported for their neuroprotective effect, such as Morinda citrifolia on pentylenetetrazol (PTZ)-induced kindling seizures in mice, by reducing the seizures and restoring behavioral and biochemical changes, although the mechanism is not described.Purpose: To evaluate the binding affinity and stability of phytoconstituents in M. citrifolia fruits toward human MGL (PDB ID 3PE6), compared to the known MGL inhibitors (JZL195 and ZYH). The in silico pharmacology study was validated by an in vitro study of the phytosterols and the ethanol extract of M. citrifolia fruits (EEMC) towards MGL.Methods: Initially, nine phytoconstituents of M. citrifolia fruits were docked to the catalytic pocket of human MGL (PDB ID: 3PE6), and compounds with the best affinity were subjected to a molecular dynamic (MD) simulation. The in vitro study was performed using the MGL inhibitor screening assay kit.Results: The best binding affinity and stability toward human MGL were shown by stigmasterol and beta-sitosterol, and the MM-PBSA total binding energy of stigmasterol and beta-sitosterol to MGL is stronger than that of JZL195 and ZYH. Moreover, beta-sitosterol and EEMC inhibit MGL with an IC50 value of, respectively, 8.10 μg/mL and 196.20 μg/mL, while JZL195 shows an IC50 of 0.028 μg/mL.Conclusion: Beta-sitosterol of Morinda citrifolia fruits may have the potential to protect human neurons by occupying the catalytic site of human MGL, thus competitively inhibiting the substrate of the enzyme. However, the inhibitory activity towards human MGL is lower than JZL195.Keywords: 2-arachidonoylglycerol, beta-sitosterol, phytosterols, prostaglandin, serine hydrolase, stigmasterol